Um olhar sobre a constituição dos saberes do trabalho dos leituristas de hidrômetros - Rodrigues, Ângela Beatriz Cavalli (Universidade do Vale do Rio do Sinos, 2006)
This paper is the result of a research undertaken for master degree certification. It was done at the Post Graduation Program on Education in the Universidade do Vale do Rio dos Sinos – UNISINOS. The research is set in the field of work and education studies and takes into account that the workplace is an educational place. Through a qualitative research, it investigates the workplace learning of thirteen public workers responsible for the water consume-reading of Capital of the Brazilian State of Rio Grande do Sul, Porto Alegre. For research data comprehension and analysis, a review of literature of some authors who have studied about education, knowledge and work was done; authors such as Acácia Eneida Kuenzer, Bernard Charlot, Eloísa Helena Santos and Miguel Arroyo, among others. Thus, this research aims to contribute with recent studies about prescript and real knowledge produced at the workplace, taking them from the public area starting-point
Keywords: princípio educativo; saberes; servidor público; trabalho; qualificação profissional; educational starting-point; knowledge; public worker; Working; professional qualification; Ciências Humanas